Preparation of hydrogels and uses thereof
A hydrogel composed of polymers A and B with amide bonds and functional molecules addresses the limitations of traditional hydrogels by providing strong adhesion, shear resistance, and biodegradability, enhancing tissue engineering and medical adhesive applications.
Patent Information
- Application Number
- CN202310704935.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
AI Technical Summary
Traditional hydrogels lack sufficient mechanical properties, biocompatibility, and dynamic adaptability, limiting their application in tissue engineering and medical adhesives, particularly in soft tissue bonding and ophthalmic surgery, where existing adhesives face issues with biocompatibility, adhesion strength, and suitability for emergency use.
A hydrogel composed of two polymers A and B, formed by amide bonds between lysine and glutamic acid, with functional molecules like peptides and phenylboronic acid structures, offering adjustable mechanical properties, excellent tissue adhesion, and biodegradability, suitable for wound repair and surgical applications.
The hydrogel provides strong adhesion, shear resistance, visible light transmittance, and biodegradability, making it suitable for skin wounds, conjunctival and corneal transplants, and bone repair, with improved clinical outcomes and reduced complications.
Smart Images

Figure BDA0004285532870000031 
Figure FDA0004285532860000011 
Figure FDA0004285532860000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomaterials and biomedicine, and in particular relates to the preparation and application of a hydrogel. Background Art
[0002] Hydrogels are a type of three-dimensional network composed of hydrophilic polymer chains that are cross-linked to form a matrix with a high water content (Annabi N., Tamayol A., Uquillas JA, et al. 25th Anniversary Article: Rational Design and Applications of Hydrogels in Regenerative Medicine [J]. Advanced Materials, 2014, 26 (1): 85-124.). Since the polymer backbone in the hydrogel has a hydrophilic part, a large amount of water can be retained inside the hydrogel material, so it has similar physical and chemical properties to liquid water, while exhibiting macroscopic solid-like rheological behavior (Guan Q.-F., Yang H.-B., Han Z.-M., et al. Sustainable Cellulose-Nanofiber-Based Hydrogels[J]. ACS Nano, 2021, 15(5): 7889-7898 & Davidson M.D., Ban E., Schoonen ACM, et al. Mechanochemical Adhesion and Plasticity in Multifiber Hydrogel Networks[J]. Advanced Materials, 2020, 32(8): 1905719.). Hydrogels have become advanced materials for new applications, ranging from drug delivery to wound dressing healing, contact lenses for enhanced vision, food, tissue engineering, and many other technical applications. Many parts of the human body contain hydrogels in the form of extracellular matrix, collagen, mucus, gelatin, cartilage, meniscus, epidermis, vitreous humor, and tendons. The hydrophilicity and 3D structure of hydrogels give them the ability to hold large amounts of water or biological fluids. Hydrogels consist of a dynamic cross-linked structure, which enables them to maintain the integrity of the hydrogel network.This property of hydrogels allows them to mimic many properties of the extracellular matrix in tissues (Brown TE, Anseth KSSpatiotemporal hydrogel biomaterials forregenerative medicine[J].Chemical Society Reviews, 2017, 46(21):6532-6552&Thiele J., Ma Y., Bruekers SMC, et al.25th Anniversary Article:Designer Hydrogels for Cell Cultures:A Materials Selection Guide[J].Advanced Materials, 2014, 26(1):125-148.), and they are widely used in tissue engineering and biomedical applications.
[0003] Macroscopic hydrogel materials formed by sugar-based macromolecules can be used in tissue engineering applications. The natural extracellular matrix (ECM) is composed of a complex network of biomacromolecules surrounding cells. On the one hand, ECM provides different mechanical properties in different tissues, which is very important for stabilizing tissue structure and mechanics; on the other hand, ECM has a complex macromolecular composition and can provide many biologically active signals to the cells surrounded by it. The characteristics of ECM in both mechanical properties and biochemical signals play an important role in regulating various cell behaviors (Frantz C., Stewart KM, Weaver V.M. The extracellular matrix at a glance [J]. Journal of Cell Science, 2010, 123 (24): 4195-4200.). Sugar-based macromolecular materials have special advantages as tissue engineering scaffolds. They can not only provide adjustable mechanical properties by virtue of their rich chemical structure and supramolecular effects, but also provide biochemical signals that mediate cell-scaffold interactions as bioactive molecules. Therefore, sugar-based macromolecular materials can act as ideal ECM mimics to construct biomaterial scaffolds to regulate related cell behaviors and promote tissue regeneration (O'Brien F.J. Biomaterials & scaffolds for tissue engineering [J]. Materials Today, 2011, 14 (3): 88-95 & Place ES, Evans ND, Stevens MM Complexity in biomaterials for tissue engineering [J]. Nature Materials, 2009, 8 (6): 457-470.).
[0004] Traditional hydrogels use synthetic polymers as raw materials, such as polyethylene glycol, polyvinyl alcohol, poly (2-hydroxyethyl methacrylate) and polyacrylamide, etc., and are cross-linked by chemical reactions. These hydrogels usually exhibit high mechanical properties and have certain degradation capabilities. However, traditional hydrogels generally lack biological activity and have limited biocompatibility. The covalent cross-linking method makes them lack dynamic adaptability to cells, and they usually have low adhesion strength to wet surfaces and biological tissues (Zhao Y., Song S., Ren X., et al. Supramolecular Adhesive Hydrogels for Tissue Engineering Applications [J]. Chemical Reviews, 2022, 122 (6): 5604-5640.). Various hydrogels based on alginate, collagen, agarose, hyaluronic acid and chitosan can be prepared by physical cross-linking methods using natural biomacromolecules. They have better biocompatibility and certain biological activity, but the lack of sufficient mechanical properties of these materials greatly limits their application range (Li Y., Rodrigues J., Tomás H. Injectable and biodegradable hydrogels: gelation, biodegradation and biomedical applications [J]. Chemical Society Reviews, 2012, 41 (6): 2193-2221.).
[0005] Mooney et al. developed a double network polymer hydrogel that simultaneously forms an ionic interaction crosslinking and a covalent crosslinking network. The strength of the gel has been significantly improved, and it can withstand deformation that exceeds 20 times its initial length, and the fracture energy is greatly improved. However, the presence of polyacrylamide and covalent crosslinking in the gel network still reduces its degradation performance and dynamic stress relaxation performance (Sun J.-Y., Zhao X., Illeperuma WRK, et al. Highly stretchable and tough hydrogels [J]. Nature, 2012, 489 (7414): 133-136.). The range of modulus adjustment of existing supramolecular hydrogels is generally narrow, and the strength of different tissues varies greatly. The modulus range of supramolecular hydrogels cannot meet the strength requirements of tissue repair.
[0006] With the continuous development of science and technology and medical level, as well as people's increasing requirements for the quality and efficiency of medical treatment, there are more and more types of medical adhesives, which can be mainly divided into two categories, namely soft tissue adhesives and hard tissue adhesives. Soft tissue adhesives can be used for bonding of skin, organs, nerves, blood vessels, mucous membranes and other parts. They mostly use medical α-cyanoacrylate glue and fibrin bio-glue. Since fibrin bio-glue is produced in the blood, there is a possibility of mutual transmission of infectious diseases such as hepatitis and AIDS during use. Although autologous blood can be used, it is not suitable for emergency treatment, and its strength and speed are not ideal. Among them, ophthalmic surgery is the fundamental clinical means to solve a variety of eye diseases. Suture suturing is currently the standard method for repairing eye incisions, but it is prone to cause postoperative complications such as irritation and inflammation. In order to overcome the shortcomings of traditional sutures, medical gel adhesives have gradually developed in recent years. Commonly used adhesives include (Baxter AG), However, they all have limitations such as poor biocompatibility, weak adhesion strength or the need for low-temperature storage, and cannot meet the requirements of actual clinical applications. Summary of the invention
[0007] In a first aspect, the present invention provides a hydrogel, which is composed of two polymers A and B, wherein the main chains of the two polymers A and B are composed of amide bonds formed by lysine and glutamic acid through polycondensation, and the value of n is 8-100; the two polymers A and B are polymers having any branching number respectively; the structural formulas of the two polymers A and B are shown in a and b:
[0008]
[0009] Ra on the main chains of the two polymers A and B is selected from (c) or (d), and the structural formulas are shown in (c) and (d):
[0010] or
[0011] Where R a1 Exogenous functional molecules are connected to the alkynyl terminals on the main chains of polymers A and B; Rb is a branched structure at the amino terminal of the side chain on the backbones of polymers A and B; Rc is a monosaccharide or oligosaccharide connected to the Rb terminal of polymer A; and Rd is an arbitrary phenylboronic acid structure compound connected to the Rb terminal of polymer B.
[0012] Furthermore, the functional molecules are selected from one or more of peptides, fluorescent groups, antibacterial molecules, growth factors, functional oligosaccharides or polysaccharides.
[0013] Furthermore, the peptide segment is selected from cell adhesive peptides, antimicrobial peptides, hormone peptides, immunomodulatory peptides, and antioxidant peptides, and the functional oligosaccharide or polysaccharide can be one or more of glycosaminoglycan, fucoidan, alginate, hyaluronic acid, and chitosan.
[0014] Furthermore, the Rb branched structure is a branching reaction that can be performed on the amino ends of the side chains of the two polymers A and B.
[0015] Furthermore, the branching generation number is preferably 0-5 generations.
[0016] Furthermore, the branching of the amino terminal is carried out by using a compound containing an amino group to increase the number of the amino terminal.
[0017] Further, the branching method is selected from the branching method using a compound containing at least two amino groups and one carboxyl group or a branching method using a substance that forms a polyamidoamine;
[0018] Furthermore, the compound can be selected from one or more of lysine, diaminopropionic acid, diaminobutyric acid, diaminobutyric acid, diaminohexanoic acid, and diaminoheptanoic acid.
[0019] Furthermore, the amino termini of the branched structure of the polymer A can be connected to different types of monosaccharides or oligosaccharides respectively.
[0020] Furthermore, the monosaccharide can be selected from one or more of mannose, glucose, galactose, fructose, xylose, fucose, gulose, idose, lyxose, mannuronic acid, glucuronic acid, galacturonic acid, guluronic acid and the like and their derivatives.
[0021] Furthermore, the oligosaccharide may be one or more of any oligosaccharide.
[0022] Furthermore, the amino terminal of the branched structure of the polymer B is connected to any phenylboronic acid structure, including one or more of phenylboronic acid half ester and carbonylphenylboronic acid half ester.
[0023] Furthermore, the A and B polymers in the hydrogel are mixed in a solution with a solid content of 10%-20%.
[0024] Furthermore, the ratio of polymer A to polymer B in the hydrogel is 1-2:2-1.
[0025] Furthermore, the strength of the hydrogel is 10Pa-100000Pa.
[0026] Furthermore, the hydrogel has excellent tissue adhesion, shear resistance, visible light transmittance and / or biodegradability.
[0027] In a second aspect, the present invention provides use of the hydrogel described in the first aspect in preparing skin wound material.
[0028] Furthermore, the skin trauma refers to trauma to the skin or mucous membrane caused by burns, mechanical damage or inflammation, and the mucous membrane includes oral mucosa or nasal mucosa, etc.
[0029] Furthermore, the substance for repairing wounds may be a drug or a medical device.
[0030] In a third aspect, the present invention provides use of the hydrogel described in the first aspect in preparing a suture required for conjunctival transplantation or corneal transplantation.
[0031] Furthermore, the use may be to improve the adhesion of conjunctival transplantation or corneal transplantation in situ and the closure of wounds.
[0032] Furthermore, the use may also be to be used as a suture agent to replace sutures.
[0033] In a fourth aspect, the present invention provides a medical preparation comprising the hydrogel according to the first aspect of the present invention.
[0034] Furthermore, the preparation also contains anti-inflammatory, hemostatic and other preparations and pharmaceutical excipients.
[0035] In a fifth aspect, the present invention provides a use of the hydrogel described in the first aspect in preparing a bone repair material.
[0036] Furthermore, the bone repair includes but is not limited to trauma, spine, joint, orthopedics, etc.
[0037] In a sixth aspect, the present invention provides a method for preparing the hydrogel according to the first aspect:
[0038] S1. Preparation of intermediate 1:
[0039] The raw materials Boc-Lys(Boc)-OH and H-Glc(OMe)-OMe·HCl underwent condensation reaction under the action of reagents EDC, HOBT and DIPEA to obtain the intermediate product 1.
[0040] S2. Preparation of intermediate product 2:
[0041] Intermediate product 1 undergoes a deprotection reaction under the action of a reagent, hydrogen chloride ethyl acetate solution, to obtain intermediate product 2.
[0042] S3. Preparation of intermediate product 3:
[0043] Intermediate product 2 and raw material Boc-Lys(Boc)-OH undergo condensation reaction under the action of reagents EDC, HOBT, and DIPEA to obtain intermediate product 3.
[0044] S4. Preparation of intermediate products 4 and 5:
[0045] Intermediate product 1 or 3 undergoes a deprotection reaction under the action of lithium hydroxide reagent to obtain intermediate product 4 or 5, respectively.
[0046] S5. Preparation of intermediate products 6, 7, and 8:
[0047] The raw material Boc-Glc-OH or the intermediate product 4 or 5 and the raw material pentafluorophenol undergo condensation reaction under the action of the reagent EDC to obtain the intermediate products 6, 7, and 8, respectively.
[0048] S6. Preparation of intermediate product 9:
[0049] The raw material Boc-Lys(Boc)-OH and propargylamine reacted with the reagents EDC, HOBT and DIPEA to obtain the intermediate product 9.
[0050] S7. Preparation of intermediate product 10 (Mb):
[0051] Intermediate product 9 was deprotected by hydrogen chloride ethyl acetate solution to obtain intermediate product 10 (Mb).
[0052] S8. Preparation of intermediate product 11 (Mc):
[0053] The raw materials Boc-aminoacetic acid and pentafluorophenol underwent condensation reaction under the action of the reagent EDC to obtain the intermediate product 11 (Mc).
[0054] S9. Preparation of intermediates 12, 13, 14:
[0055] Intermediate product 6 or 7 or 8 and intermediate product 10 (Mb) undergo polymerization reaction under the action of reagent DIPEA to obtain intermediate products 12, 13, and 14.
[0056] S10. Preparation of intermediates 15, 16, and 17:
[0057] Intermediate product 12, 13 or 14 undergoes deprotection reaction under the action of trifluoroacetic acid to obtain intermediate products 15, 16 and 17, respectively.
[0058] Preparation of S11.B component (products 18, 19, 20):
[0059] The intermediate product 15 or 16 or 17 reacts with the raw material Bob under the action of the reagent sodium borohydride to obtain the product B component (product 18, 19, 20).
[0060] S12. Preparation of intermediates 21, 22, and 23:
[0061] Intermediate 15 or 16 or 17 and intermediate 11 (Mc) undergo condensation reaction under the action of reagent DIPEA, and further undergo deprotection reaction under the action of reagent trifluoroacetic acid to obtain intermediates 21, 22, and 23, respectively.
[0062] Preparation of S13.A component (products 24, 25, 26):
[0063] The intermediate product 21 or 22 or 23 and the raw material monosaccharide or oligosaccharide undergo condensation reaction under the action of the reagent aniline to obtain product A component (product 24, 25, 26) respectively;
[0064] S14. Synthesis of Hydrogel
[0065] The solid content of component A or component B is prepared at 12wt% to 20wt%. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 Molecular structures of raw material A and B components
[0067] Figure 2 Branching structural changes in group A / B
[0068] Figure 3 Synthetic routes of intermediates M0-a, M1-a, M2-a, Mb, Mc
[0069] Figure 4 1 HNMR result of 1
[0070] Figure 5 1 HNMR result of 2
[0071] Figure 61H NMR result of 3
[0072] Figure 7 1 HNMR result of4
[0073] Figure 8 1 HNMR result of5
[0074] Fig. 9 1 HNMR result of6
[0075] Fig.10 1 HNMR result of7
[0076] Fig.11 1 HNMR result of8
[0077] Fig.12 1 HNMR result of 9
[0078] Fig.13 1 HNMR result of 10
[0079] Fig.14 1 HNMR result of 11
[0080] Fig.15 Synthesis routes of P0, P1, P2, component A (P0-Man(Glc), P1-Man(Glc), P2-Man(Glc)), and component B (P0-Bob, P1-Bob, P2-Bob)
[0081] Fig.16 1 HNMR result of 12
[0082] Fig.17 1 HNMR result of 15
[0083] Fig.18 1 HNMR result of compound 16
[0084] Fig.19 1 HNMR result of compound 17
[0085] Fig. 20 1 HNMR result of 18
[0086] Fig.21 1 HNMR result of 19
[0087] Fig. 22 1 HNMR result of 20
[0088] Fig.23 1 HNMR result of 21
[0089] Fig.24 1 HNMR result of 22
[0090] Fig.251 HNMR result of 23
[0091] Fig.26 1 HNMR result of 24(P0-Man)
[0092] Fig. 27 1 HNMR result of 25(P1-Man)
[0093] Fig.28 1 HNMR result of 25(P1-Glc)
[0094] Fig.29 1 HNMR result of 26(P2-Man)
[0095] Fig.30 Synthetic routes of polymers P0-Bob-1, P1-Bob-1, and P2-Bob-1 with replaced phenylboronic acid ester structures
[0096] Fig.31 1 HNMR result of P1-Bob-1
[0097] Fig.32 1 H NMR results of 30(P2-Man-RGD)
[0098] Fig.33 Synthetic routes of polymers G0, G1 and G2 with different branching patterns
[0099] Fig.34 1 HNMR result of G0.5
[0100] Fig.35 1 HNMR result of G1.0
[0101] Fig.36 1 HNMR result of G1.5
[0102] Fig.37 1 HNMR result of G2.0
[0103] Fig.38Tissue adhesion strength ((a) P0-Man+P0-Bob, P1-Man+P1-Bob, P2-Man+P2-Bob; (b) P2-Man+P0-Bob, P2-Man+P0-Bob, P2-Man+P2-Bob; (c) P1-Bob+P1-Glc, P1-Bob+P1-Man) Fig.39 Shear resistance test
[0104] Fig.40 Mechanical strength of hyperbranched polypeptide hydrogels constructed under the same branching system conditions with a solid content of 12 wt% (a) P0-Man+P0-Bob (b) P1-Man+P1-Bob (c) P2-Man+P2-Bob
[0105] Fig.41 Mechanical strength of hyperbranched polypeptide hydrogels constructed under different branching system conditions with solid content of 12wt% (a) P2-Man+P2-Bob (b) P2-Man+P1-Bob (c) P0-Man+P0-Bob (d) P1-Man+P0-Bob (e) P2-Man+P0-Bob
[0106] Fig.42 Mechanical strength of gel formed by P1-Glc+P1-Bob and P1-Man+P1-Bob in neutral state
[0107] Fig.43 Test of hydrogel adhesion stability to pig skin in vitro under external force
[0108] Fig.44 Underwater test Gel adhesion stability test
[0109] Fig.45 Light transmittance test
[0110] Fig.46 In vitro degradation assay
[0111] Fig.47 Gel autologous conjunctival transplantation test
[0112] Fig.48 Biomechanical testing of hydrogel sealing corneal incision in pig eyes in vitro
[0113] Fig.49 Biosafety Testing
[0114] Fig.50 Cell safety testing
[0115] Fig.51 Rabbit autologous conjunctival transplantation experiment
[0116] Fig.52Effect of corneal injury repair in animal models of corneal injury repair
[0117] Fig.53 Bone defect repair effect in animal models of bone defect repair DETAILED DESCRIPTION
[0118] Example 1 Synthesis of hydrogel pre-materials
[0119] In this embodiment, the raw materials required for the synthesis of the hydrogel include Boc-L-glutamic acid (Boc-Glc-OH), (S)-2,6-di-tert-butyloxycarbonylaminocaproic acid (Boc-Lys(Boc)-OH), L-glutamic acid dimethyl ester hydrochloride (H-Glc(OMe)-OMe·HCl), pentafluorophenol, mannose (or different types of monosaccharides or oligosaccharides), phenylboronic acid half ester (Bob), Boc-aminoacetic acid, and propargylamine; all of which are commercially available.
[0120] The required reagents include 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 1-hydroxybenzotriazole (HOBT), N,N-diisopropylethylamine (DIPEA), lithium hydroxide, hydrogen chloride ethyl acetate solution, sodium borohydride, trifluoroacetic acid, anhydrous ether, and aniline, all of which are commercially available.
[0121] 1.1 Molecular structure
[0122] 1.1.1 Basic structure of raw material molecules
[0123] The structure diagram of raw material A component and raw material B component is as follows: Figure 1 shown.
[0124] 1.2 Molecular expansion structure
[0125] 1.2.1 Changes in branching structure in group A / B Figure 2 .
[0126] 1.2.2 Changes in sugar content of component A
[0127] R=Mannose (Man)Or R=Glucose (Glc)
[0128] 1.3 Preparation and characterization of components A and B
[0129] 1.3.1 Preparation of intermediates M0-a, M1-a, M2-a, Mb, Mc (see Figure 3 );
[0130] 1. Synthesis of Compound 1
[0131] (1) Boc-Lys(Boc)-OH, EDC, HOBT and H-Glc(OMe)-OMe·HCl were dissolved in dry dichloromethane.
[0132] (2) Slowly add DIPEA or triethylamine dropwise in an ice-water bath. The ratio of the raw materials is Boc-Lys(Boc)-OH:EDC:HOBT:H-Glc(OMe)-OMe·HCl:DIPEA or triethylamine = 1:1:1:1:1.
[0133] (3) Remove the ice-water bath and continue stirring for 6 to 36 hours. After the reaction is completed, wash with dilute hydrochloric acid, dilute sodium hydroxide, and saturated brine. After separating the organic phase, the crude product is separated and purified by silica gel column chromatography to obtain a white solid (see Figure 4 ).
[0134] 2. Synthesis of Compound 2
[0135] (1) In an ice-water bath, slowly add excess saturated hydrogen chloride ethyl acetate solution dropwise to compound 1.
[0136] (2) Remove the ice-water bath and stir the mixture for 30 min. A large amount of white precipitate is produced during the reaction.
[0137] (3) After the reaction was completed, a white solid was obtained by filtration, which was washed several times with ethyl acetate and then dried under vacuum at room temperature to obtain a white solid (see Figure 5 ).
[0138] 3. Synthesis of Compound 3
[0139] (1) Dissolve Boc-Lys(Boc)-OH, EDC, HOBT and compound 2 in dry dichloromethane.
[0140] (2) In an ice-water bath, slowly add DIPEA or triethylamine dropwise, and the ratio of the raw materials is compound 2: Boc-Lys(Boc)-OH: EDC: HOBT: DIPEA or triethylamine = 1: 2: 2: 2: 2. Remove the ice-water bath and continue stirring the reaction for 24 hours.
[0141] (3) After the reaction, the mixture was washed with dilute hydrochloric acid, dilute sodium hydroxide and saturated brine respectively. The organic phase was separated, dried over anhydrous magnesium sulfate, filtered and spin-dried. The crude product was separated and purified by silica gel column chromatography to obtain a white solid (see Figure 6 ).
[0142] 4. Synthesis of Compound 5
[0143] (1) Compound 1 or 3 was dissolved in a mixed solvent of methanol / water = 4:1.
[0144] (2) Under ice water bath conditions, slowly add lithium hydroxide or sodium hydroxide or potassium hydroxide, and the ratio of the raw materials is compound 1 or 3: lithium hydroxide or sodium hydroxide or potassium hydroxide = 1:2.
[0145] (3) Remove the ice water bath and continue the reaction for 12 h. Then add dilute hydrochloric acid to the reaction solution to adjust the pH to 5.
[0146] (4) After removing the methanol in the system under reduced pressure, the product was extracted with ethyl acetate three times, and the organic phases were combined and dried by spin drying to finally obtain a white product (see Figure 7 , 8).
[0147] 5. Synthesis of compounds 6 to 8 (Ma)
[0148] (1) Compound 4 or 5 or Boc-Glc-OH and EDC were dissolved in dry dichloromethane, and pentafluorophenol was slowly added in an ice-water bath.
[0149] (2) The ratio of the raw materials is compound 4 or 5 or Boc-Glc-OH: EDC: pentafluorophenol = 1:2:2. After removing the ice-water bath, the reaction is stirred at room temperature for 12 hours.
[0150] (3) After the reaction was completed, the excess solvent was removed by distillation under reduced pressure, and the crude product was separated by silica gel column chromatography to obtain a white solid (see Fig. 9 , 10, 11).
[0151] 6. Synthesis of Compound 9
[0152] (1) Dissolve Boc-Lys(Boc)-OH, EDC, HOBT and propargylamine in dry dichloromethane. Slowly add DIPEA or triethylamine dropwise in an ice-water bath.
[0153] (2) The ratio of the raw materials is Boc-Lys(Boc)-OH:EDC:HOBT:propargylamine:DIPEA or triethylamine = 1:1:1:1:1. After removing the ice water bath, the reaction is continued for 24 hours.
[0154] (3) After the reaction is completed, the system is washed with dilute hydrochloric acid and dilute sodium hydroxide solution, and the organic phase is separated. The crude product is separated and purified by silica gel column chromatography to obtain the product (see Fig.12 )).
[0155] 7. Synthesis of Compound 10 (Mb)
[0156] (1) Compound 9 was cooled in an ice-water bath, and then an excess of hydrogen chloride saturated ethyl acetate solution was slowly added dropwise to dissolve it. The ice-water bath was removed and the reaction was continued for 0.5 to 6 hours.
[0157] (2) After the reaction is completed, a white solid is obtained by filtration, which is washed several times with ethyl acetate and then dried under vacuum to obtain the product (see Fig.13 ).
[0158] 8. Synthesis of Compound 11 (Mc):
[0159] (1) Dissolve Boc-aminoacetic acid and EDC in dry dichloromethane. Slowly add pentafluorophenol in an ice-water bath. The molar ratio of the raw materials is Boc-aminoacetic acid: EDC: pentafluorophenol = 1:1:1.
[0160] (2) After removing the ice water bath, continue stirring the reaction for 24 hours. After the reaction is completed, filter out the precipitate, wash it several times with dichloromethane, and dry it in vacuum to obtain a white product (see Fig.14 ).
[0161] 1.4 Preparation and characterization of P0, P1, P2, A component (including A component with sugar molecules changed to glucose) (P0-Man(Glc), P1-Man(Glc), P2-Man(Glc)), and B component (P0-Bob, P1-Bob, P2-Bob) (synthetic route see Fig.15 )
[0162] 1.4.1 Synthesis of compounds 12, 13, 14 (P0, P1, P2)
[0163] (1) Compound 6, 7, or 8 and Compound 10 are slowly dissolved in anhydrous DMSO or DMF. DIPEA or triethylamine is slowly added dropwise in an ice-water bath.
[0164] (2) The ratio of the raw materials is compound 6 or 7 or 8: compound 10: DIPEA or triethylamine = 1:1:2. After removing the ice-water bath, continue stirring the reaction for 48 hours.
[0165] (3) After the reaction is completed, add methanol or ethanol to dilute the solution under ice water bath conditions, then precipitate the product in ether and centrifuge. Repeat this step 3 times, and finally filter out the precipitate and vacuum dry to obtain the product (see Fig.16 ).
[0166] 1.4.2 Synthesis of compounds 15, 16, and 17
[0167] (1) Compound 12, 13 or 14 was dissolved in excess trifluoroacetic acid in an ice-water bath. After removing the ice-water bath, stirring was continued for 4.5 h.
[0168] (2) After the reaction, the solution was diluted with methanol, the product was precipitated in ether, the product was filtered out, washed with ether several times, and then vacuum dried to obtain a white product (see Fig.17 , 18, 19).
[0169] 1.4.3 Synthesis of compounds 19 and 20 (P0-Bob, P1-Bob, P2-Bob)
[0170] (1) Add compound 15, 16 or 17, phenylboronic acid half ester and sodium borohydride into a flask and evacuate the mixture.
[0171] (2) The ratio of the raw materials is compound 15 or 16 or 17: phenylboronic acid half ester: sodium borohydride = 1:1:4.
[0172] (3) Then, methanol was slowly added dropwise under ice-water bath conditions. The ice-water bath was then removed and the reaction was continued with stirring for 24 h.
[0173] (4) After the reaction, the mixture was dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of less than 2000 and freeze-dried to obtain a white solid (see Fig. 20 , 21, 22).
[0174] 1.4.4 Synthesis of compounds 21, 22, and 23
[0175] (1) Compound 15, 16 or 17 and compound 11 (Mc) were dissolved in anhydrous DMSO or DMF.
[0176] (2) In an ice-water bath, slowly add DIPEA or triethylamine dropwise. The ratio of the raw materials is compound 15 or 16 or 17: compound 11: DIPEA or triethylamine = 1:1:2.
[0177] (3) Remove the ice-water bath and continue stirring the reaction for 24 h.
[0178] (4) After the reaction is completed, the solution is diluted with methanol under ice-water bath conditions, and the product is precipitated with ether. This process is repeated three times, and finally the precipitate is filtered out and the white solid is dried under vacuum at room temperature.
[0179] (5) Then, the solid was dissolved in excess trifluoroacetic acid in an ice-water bath. The ice-water bath was removed and stirring was continued for 4.5 h.
[0180] (6) After the reaction is completed, dilute with methanol in an ice-water bath and separate the product by precipitating with ether. Filter out and wash with ether several times and dry under vacuum at room temperature to obtain a white solid (see Fig.23 , 24, 25).
[0181] 1.4.5 Synthesis of compounds 24, 25, 26 (P0-Man(Glc), P1-Man(Glc), P2-Man(Glc) (synthetic route see Fig.30 )
[0182] (1) Compound 21, 22 or 23, mannose (glucose) and 10-100 μL of aniline were dissolved in an acetic acid / sodium acetate buffer solution at pH 4.2 and stirred at 37° C. for 6-24 h.
[0183] (2) The ratio of the raw material substances is compound 21 or 22 or 23: mannose (glucose) = 1:1.
[0184] (3) Dialyze using a dialysis bag with a molecular weight cutoff of less than 2000 and freeze-dry to obtain a white solid (26, 27, 28, 29, 30). 1.4.6 Synthesis of compound 27 (P0-Bob-1)
[0185] (1) Compound 15 (0.155 g, 0.53 mmol) and Bob-1 (0.199 g, 0.58 mmol) were dissolved in 1.5 mL of anhydrous DMF. After cooling in an ice-water bath, DIPEA (0.3 mL, 1.63 mmol) was slowly added dropwise to the system. The ice-water bath was removed and stirred for 6 h. After the reaction was completed, the reaction system was diluted with 5 mL of methanol and then precipitated with 250 mL of ether. This step was repeated 3 times to fully remove DIPEA. Finally, the product was dried in vacuum to obtain a white solid (0.197 g, 82%).
[0186] 1.4.7 Synthesis of Compound 28 (P1-Bob-1)
[0187] (1) Compound 16 (0.165 g, 0.39 mmol) and Bob-1 (0.295 g, 0.86 mmol) were dissolved in 1.5 mL of anhydrous DMSO. After cooling in an ice-water bath, DIPEA (0.3 mL, 1.63 mmol) was slowly added dropwise to the system. The ice-water bath was removed and the mixture was stirred for 6 h.
[0188] (2) After the reaction is completed, the reaction system is diluted with 5 mL of methanol and then precipitated with 250 mL of ether. This step is repeated 2 to 3 times to fully remove DIPEA.
[0189] (3) The product was finally dried under vacuum to obtain a white solid (0.219 g, 76%).
[0190] 1.4.8 Synthesis of Compound 29 (P2-Bob-1)
[0191] (1) Compound 17 (0.130 g, 0.19 mmol) and Bob-1 (0.297 g, 0.86 mmol) were dissolved in 1.5 mL of anhydrous DMF. After cooling in an ice-water bath, DIPEA (0.3 mL, 1.63 mmol) was slowly added dropwise to the system. The ice-water bath was removed and the mixture was stirred for 6 h.
[0192] (2) After the reaction, the reaction system was diluted with 5 mL of methanol and then precipitated with 250 mL of ether. This step was repeated 3 times to fully remove DIPEA. Finally, the product was vacuum dried to obtain a white solid (0.182 g, 72%) (see Fig.31 ).
[0193] 1.4.9 Synthesis of compound 30 (P2-Man-RGD)
[0194] (1) Compound 26, N3-GRGDSP peptide, DMF, cuprous bromide, and PMDETA were added to a flask and deoxygenated.
[0195] (2) Heat to 50 degrees Celsius and continue stirring the reaction for 24 hours.
[0196] (3) After the reaction is completed, the solution is dialyzed in deionized water using a dialysis bag with a molecular weight cutoff of less than 2000 and freeze-dried to obtain a white solid.
[0197] White solid product P2-Man-RGD( Fig.32 ).
[0198] 1.5 Preparation and characterization of G0, G1, and G2 with different branching patterns (see Fig.33 )
[0199] 1.5.1 Synthesis of G1.0
[0200] (1) The polymer main chain G0 and the monomer methyl acrylate MA are dissolved in anhydrous methanol at room temperature, and then the methanol solution of G0 is slowly dripped into the methanol solution of MA. The molar ratio of the raw materials is G0 (n-NH2): MA = 1:30.
[0201] (2) After the addition was completed, the mixture was stirred at room temperature for 48 hours. After the reaction was completed, the unreacted MA and the solvent methanol were dried by spin drying to obtain the product G0.5.
[0202] (3) G0.5 and the reaction raw material ethylenediamine were then dissolved in anhydrous methanol at room temperature, and then the methanol solution of G0.5 was slowly dripped into the methanol solution of ethylenediamine. The molar ratio of the raw materials was G0.5 (n-COOR): ethylenediamine = 1:50.
[0203] (4) After the addition was completed, the reaction was stirred at room temperature for 48 hours. After the reaction was completed, the unreacted ethylenediamine and the solvent methanol were dried by spin drying to obtain the product G1.0 (see Fig.34 , 35).
[0204] 1.5.2 Synthesis of G2.0
[0205] (1) The polymer G1.0 and the monomer methyl acrylate MA were dissolved in anhydrous methanol at room temperature, and then the methanol solution of G0 was slowly dripped into the methanol solution of MA, and the molar ratio of the raw materials was G1.0 (n-NH2): MA = 1:50. After the dripping was completed, the reaction was stirred at room temperature for 48 hours.
[0206] (2) After the reaction was completed, the unreacted MA and the solvent methanol were dried by spin drying to obtain the product G1.5 (see Fig.36 ). Subsequently, G1.5 and the reaction raw material ethylenediamine were dissolved in anhydrous methanol at room temperature, and then the methanol solution of G1.5 was slowly dripped into the methanol solution of ethylenediamine. The molar ratio of the raw materials was G1.5 (n-COOR): ethylenediamine = 1:50.
[0207] (3) After the addition was completed, the reaction was stirred at room temperature for 48 hours. After the reaction was completed, the unreacted ethylenediamine and the solvent methanol were dried by spin drying to obtain the product G2.0 (see Fig.37 ).
[0208] Example 2 Hydrogel Preparation and Properties
[0209] 2.1 Gel preparation method
[0210] First, polymer solutions of component A (Pn-Man, Pn-Glc (n=0, 1, 2)) and component B (Pn-Bob (n=0, 1, 2)) are prepared: the solid content of A and B solutions is controlled to be 12wt% to 20wt%. Hyperbranched glycopeptide polymers (P0-Man, P1-Man, P2-Man) are respectively dissolved in pure water to obtain component A solution, and hyperbranched phenylboronic acid half ester polypeptides (P0-Bob, P1-Bob, P2-Bob) are respectively dissolved in pure water and the pH is adjusted to 8 to obtain component B solution. The ratio of donor / acceptor (sugar unit / phenylboronic acid unit) in the A and B component solutions is regulated to be 2:1. After the two are completely dissolved in the solvent, the two solutions are evenly mixed and allowed to stand to obtain a series of hyperbranched polypeptide hydrogel materials.
[0211] 2.2 Gel performance test
[0212] 2.1.1 Hydrogel adhesion stability test
[0213] The pigskin was trimmed into 1cm×1cm size, fixed on a 1cm×4cm acrylic plate with quick-drying glue, and a total volume of 20μL of hydrogel was applied between the two pieces of pigskin. After waiting for 10 minutes for the gel to completely solidify, the two ends of the sample were fixed with a clamp, and the sample was pulled at a speed of 2mm / min using a ZP50 tensile machine until it was completely separated, and the maximum tissue adhesion strength reached before the sample was completely separated was recorded.
[0214] The experimental results of the binding ability of the two components show that increasing the branching degree can effectively increase the number of terminal functionalized sites, thereby increasing the number of binding sites, and ultimately further increasing the molar binding enthalpy of the two, that is, the gel stability is better (see Fig.38 a, Fig.38 a,); P1-Glc+P1-Bob and P1-Man+P1-Bob have almost the same binding exotherm, indicating that their binding abilities are very similar (see Fig.38 c).
[0215] 2.1.2 Shear test
[0216] The gel can provide effective adhesion in the 1:2 and 2:1 ratio ranges, has good tissue adhesion and shear resistance, and is suitable for skin wound repair and conjunctival transplantation applications (see Fig.39 ).
[0217] The test of the rotational rheometer shows that the gel strength can be precisely controlled within the range of 10Pa to 100000Pa under different combinations of A and B (see Fig.40 , 41); According to the rotational rheometer test, when neutral, the mechanical strength of the gel formed by P1-Glc+P1-Bob and P1-Man+P1-Bob is almost the same (see Fig.42 ).
[0218] 2.1.3 Torsion test - test of hydrogel adhesion stability to pig skin in vitro under external force
[0219] First, the gel was colored with Macaus blue for subsequent observation. A total of 20 μL of the two-component polymer solution of A and B was dropped on the pig skin. After waiting for 10 minutes for the solution to completely solidify in situ to form a hydrogel, different stresses such as twisting, folding, and stretching were applied to the pig skin to observe whether the gel was stably adhered under stress, whether it fell off or cracked, and take photos.
[0220] The gel coated on the pig skin surface can remain stably attached to the pig skin surface in various deformation states without falling off or breaking. The gel has good adhesion stability (see Fig.43 ).
[0221] 2.1.4 Adhesion stability - underwater test Gel adhesion stability test
[0222] The hydrogel was colored with Macaus blue to facilitate subsequent observation. After the polymer solution was dropped on the pig skin to form a hydrogel in situ, it was placed in a PBS buffer solution (pH = 7.2) and soaked. The solution was changed every day until the 7th day. After the soaking, the sample was taken out to observe whether the gel could stably adhere to the pig skin surface after long-term soaking in water, and the adhesion stability under water flushing.
[0223] The gel can still stably adhere to the tissue surface after being immersed in water for a long time. The gel has good adhesion stability (see Fig.44 ).
[0224] 2.1.5 Light transmittance test
[0225] The preliminary results of the light transmittance test show that the visible light transmittance of the 0+0 formula is close to that of carbomer and better than that of the 1+1 formula. However, in actual imaging, the flatness of 0+0 is not as good as that of carbomer and it is easy to produce small wrinkles. Therefore, the imaging transparency is slightly inferior to that of carbomer gel (see Fig.45 ); wherein the 0+0 formula is the formula of component A (Pn-Man, Pn-Glc (n=0)) and component B (Pn-Bob (n=0)); the 1+1 formula is the formula of component A (Pn-Man, Pn-Glc (n=1)) and component B (Pn-Bob (n=1)); the 0+1 formula is the formula of component A (Pn-Man, Pn-Glc (n=1)) and component B (Pn-Bob (n=0).
[0226] 2.1.6 In vitro degradation experiment
[0227] The gel has a certain stability in a wet environment and medium- to long-term degradation (see Fig.46 ).
[0228] 2.1.7 Gel for autologous conjunctival transplantation testing
[0229] A 1 cm × 1 cm conjunctival defect was made symmetrically on the pig eyeball. In the experimental group, 12 μL of hydrogel was injected into the conjunctival defect, and the conjunctival flap was attached after waiting for 1 min; the conjunctival flap was naturally covered in the control group. Photos were taken at 0, 10, 20, 30, and 40 min, and the displacement area of the conjunctival flap was analyzed using Image J. The same conjunctival defect was further made, and the experimental group was attached with conjunctival flap hydrogel, and the control group was naturally covered with conjunctival flap. After the transplantation, the conjunctival transplantation site was rinsed with a continuous stream of water, and the transplanted conjunctival flap was observed to see if it fell off to determine the stability of adhesion.
[0230] The 0+0 and 1+1 gel formulas have good adhesion and can effectively fix the conjunctiva and sclera. The flushing experiment showed that the 0+0 and 1+1 gel formulas have good adhesion and can make the transplanted conjunctival tissue adhere to the original position without being washed away by water (see Fig.47 ).
[0231] 2.1.8 Biomechanical testing of hydrogel-sealed corneal incisions in pig eyes in vitro
[0232] According to the corneal incision closure method, pig eyes were randomly divided into 4 groups: suture group, Gel0+0 (component A (Pn-Man, Pn-Glc (n=0)) and component B (Pn-Bob (n=0))), Gel1+1 (component A (Pn-Man, Pn-Glc (n=1)) and component B (Pn-Bob (n=1)), fibrin group. The corneal flap was removed by corneal trephine under the operating microscope and placed in the artificial anterior chamber. The water inlet end of the artificial anterior chamber was connected to a microinjection tube. The injection pump was connected to the water outlet of the artificial anterior chamber. After the artificial anterior chamber was filled to 21 mmHg (normal intraocular pressure), a 2.8 mm linear incision was made near the limbus of the cornea and sclera using the corneal main incision knife. The corneal incision was closed using hydrogel, commercial fibrin glue or suture suture in the experimental group. After the operation, the microinjection pump was turned on to add liquid to the artificial anterior chamber. The pumping rate was 10 mm / h. The changes in the differential pressure gauge readings were recorded by video. When the peak value appeared, the incision was observed for liquid leakage and the readings were recorded.
[0233] The results showed that the 0+0 and 1+1 formulas had less leakage than the suture group and commercial Fibrin, had better sealing effect, and could withstand intraocular pressure above 200 mmHg. They are suitable for sealing corneal wounds (see Fig.48 ).
[0234] Example 3 Biological experiments of gel
[0235] 3.1 Biosafety Testing
[0236] SD rats were intradermally injected with 100 μl of P1Bob + 100 μl of P1Man prepared in Example 1, and samples were taken for pathological sections 2 weeks, 1 month, 2 months and 3 months after the injection.
[0237] The results showed that there was no significant difference between the experimental group and normal skin, and no obvious inflammatory reaction was induced, proving that the gel has good biocompatibility (see Fig.49 ).
[0238] The results of the cell safety test showed that the material did not affect cell activity and normal cell proliferation (see Fig.50 ).
[0239] 3.2 Rabbit autologous conjunctival transplantation
[0240] Suture, 0+0 (A component (Pn-Man, Pn-Glc (n=0)) and B component (Pn-Bob (n=0)), 1+1 (A component (Pn-Man, Pn-Glc (n=1)) and B component (Pn-Bob (n=1)), and commercial materials were compared respectively.
[0241] The preliminary results showed that the gel group played a transplantation role. The tissue at the transplant site in the gel group showed a tendency to repair. Conjunctival morphology was stratified squamous epithelium and a small amount of goblet cells. The epithelial regeneration effect was good, which was equivalent to the suture group and better than the commercial Fibrin effect (see Fig.51 ).
[0242] Example 4 Animal Model of Corneal Damage Repair
[0243] A 2.8 mm single-plane linear main incision was made near the limbus of the rabbit eye, and then nylon suture or gel closure was performed according to the group.
[0244] The results of intraocular pressure monitoring showed that the intraocular pressure of all groups basically returned to normal three days after the incision was glued, indicating that the treatment methods of all groups can effectively seal the incision and prevent anterior chamber leakage.
[0245] Anterior segment optical coherence tomography showed that the thickness of the inner and outer incisions in the Gel 1+1 (component A (Pn-Man, Pn-Glc (n=1)) and component B (Pn-Bob (n=1)) groups decreased more significantly at 3-7 days compared with the other groups, which can promote early healing of corneal tissue and disappearance of edema earlier.
[0246] The slice results showed that the Gel 1+1 group had the best repair effect, the tissue structure at the incision was continuous, and the collagen fibers in the corneal stroma were arranged regularly and had a normal structure.
[0247] In general, Gel 1+1 can effectively close the corneal incision, facilitate early corneal tissue repair and edema reduction, and help the correct morphological distribution of the cornea after surgery, with the best repair effect (see Fig.52 ).
[0248] Example 5 Bone defect repair animal model
[0249] The left femoral condyle of SD rats was used to create a bone defect with a diameter of 3 mm and a depth of 3 mm using a dental drill. Four groups of rats received the following implants to repair the bone defect:
[0250] (1) Pathological group: only debridement was performed at the defect site;
[0251] (2) Gel 1+1 (Component A (Pn-Man, Pn-Glc (n=1)) and Component B (Pn-Bob (n=1)) group: 40ul of the 1+1 gel complex was implanted in the defect;
[0252] (3) Gel 2+2 (Component A (Pn-Man, Pn-Glc (n=2)) and Component B (Pn-Bob (n=2)) group: 40ul of the 2+2 gel complex was implanted in the defect;
[0253] (4) 2+2RGD group ((Component A (Pn-Man-RGD (n=2)) and Component B (Pn-Bob (n=2))): 40ul of the 2+2RGD gel complex was implanted in the defect.
[0254] At the 4th week, the left femoral condyle of the rats was examined using Micro-CT.
[0255] CT reconstruction results show (see Fig.53 )GEL2+2 and GEL2+2RGD treatment groups significantly promoted the repair of bone tissue defects compared with the blank group and GEL1+1 group.
[0256] The above description is a general description of the present invention. According to the situation or actual needs, changes in form and substitution of equivalents can be made. Although specific terms are used herein, these terms are intended to describe rather than limit the purpose. Those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A hydrogel, the hydrogel is composed of two polymers A and B, the main chains of the two polymers A and B are composed of amide bonds formed by lysine and glutamic acid through polycondensation, and the value of n is 8-100; the two polymers A and B are polymers with arbitrary branching generations respectively; the structural formulas of the two polymers A and B are shown in a and b: Ra on the main chains of the two polymers A and B is selected from (c) or (d), and the structural formulas are shown in (c) and (d): or Where R a 1 is an exogenous functional molecule connected to the alkynyl terminal on the main chain of polymers A and B; Rb is a branched structure at the amino terminal of the side chain on the backbone of polymers A and B; Rc is a monosaccharide or oligosaccharide connected to the Rb terminal of polymer A; Rd is an arbitrary phenylboronic acid structure compound connected to the Rb terminal of polymer B.
2. The hydrogel according to claim 1, It is characterized in that The functional molecules are selected from one or more of peptides, fluorescent groups, antibacterial molecules, growth factors, functional oligosaccharides or polysaccharides.
3. The hydrogel according to claim 1, It is characterized in that The monosaccharide connected to the polymer A can be selected from one or more of mannose, glucose, galactose, fructose, xylose, fucose, gulose, idose, lyxose, mannuronic acid, glucuronic acid, galacturonic acid, guluronic acid and the like and their derivatives, and the oligosaccharide connected to the polymer A can be one or more of any oligosaccharide.
4. The hydrogel according to claim 1, It is characterized in that Any phenylboronic acid structure connected to the polymer B includes one or more of phenylboronic acid half ester and carbonyl phenylboronic acid half ester.
5. The hydrogel according to claim 1, It is characterized in that The ratio of polymer A to polymer B in the hydrogel is 1-2:2-1.
6. Use of the hydrogel according to claims 1 to 5 in the preparation of skin wound materials.
7. Use of the hydrogel according to claims 1 to 5 in preparing a suture required for conjunctival transplantation or corneal transplantation.
8. A medical preparation comprising the hydrogel according to claims 1-5.
9. Use of the hydrogel according to claims 1 to 5 in preparing bone repair materials.
10. A method for preparing the hydrogel according to claims 1-5: S1. Preparation of intermediate 1: The raw materials Boc-Lys(Boc)-OH and H-Glu(OMe)-OMe·HCl underwent condensation reaction under the action of reagents EDC, HOBT and DIPEA to obtain the intermediate product 1. S2. Preparation of intermediate product 2: Intermediate product 1 undergoes a deprotection reaction under the action of a reagent, hydrogen chloride ethyl acetate solution, to obtain intermediate product 2. S3. Preparation of intermediate product 3: Intermediate product 2 and raw material Boc-Lys(Boc)-OH undergo condensation reaction under the action of reagents EDC, HOBT, and DIPEA to obtain intermediate product 3. S4. Preparation of intermediate products 4 and 5: Intermediate product 1 or 3 undergoes a deprotection reaction under the action of lithium hydroxide reagent to obtain intermediate product 4 or 5, respectively. S5. Preparation of intermediate products 6, 7, and 8: The raw material Boc-Glu-OH or the intermediate product 4 or 5 and the raw material pentafluorophenol undergo condensation reaction under the action of the reagent EDC to obtain the intermediate products 6, 7, and 8, respectively. S6. Preparation of intermediate product 9: The raw material Boc-Lys(Boc)-OH and propargylamine reacted with the reagents EDC, HOBT and DIPEA to obtain the intermediate product 9. S7. Preparation of intermediate product 10 (Mb): Intermediate product 9 was deprotected by hydrogen chloride ethyl acetate solution to obtain intermediate product 10 (Mb). S8. Preparation of intermediate product 11 (Mc): The raw materials Boc-aminoacetic acid and pentafluorophenol underwent condensation reaction under the action of the reagent EDC to obtain the intermediate product 11 (Mc). S9. Preparation of intermediates 12, 13, 14: Intermediate product 6 or 7 or 8 and intermediate product 10 (Mb) undergo polymerization reaction under the action of reagent DIPEA to obtain intermediate products 12, 13, and 14. S10. Preparation of intermediates 15, 16, and 17: Intermediate product 12, 13 or 14 undergoes deprotection reaction under the action of trifluoroacetic acid to obtain intermediate products 15, 16 and 17, respectively. Preparation of S11.B component (products 18, 19, 20): The intermediate product 15 or 16 or 17 reacts with the raw material Bob under the action of the reagent sodium borohydride to obtain the product B component (product 18, 19, 20). S12. Preparation of intermediates 21, 22, and 23: Intermediate 15 or 16 or 17 and intermediate 11 (Mc) undergo condensation reaction under the action of reagent DIPEA, and further undergo deprotection reaction under the action of reagent trifluoroacetic acid to obtain intermediates 21, 22, and 23, respectively. Preparation of S13.A component (products 24, 25, 26): The intermediate product 21 or 22 or 23 and the raw material monosaccharide or oligosaccharide undergo condensation reaction under the action of the reagent aniline to obtain product A component (product 24, 25, 26) respectively; S14. Synthesis of Hydrogel The solid content of component A or component B is prepared at 12wt% to 20wt%.
Citation Information
Cited By
Use of glycopeptide hydrogels in treating endometrial lesions
CN122768172A
